Genital prolapse at university hospital of Cocody: clinical aspects and therapeutic management - Kakou, Charles; Adjoby, Roland; Kasse, Raoul; Assuikwe, Victorine; Mian, Boston; Boni, Serge (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: To determine the epidemiological aspects of genital prolapse; to describe the different clinical aspects of genital prolapse observed and to evaluate the therapeutic management of genital prolapse at the University hospital of Cocody (UH-C). Methods: We did an observational and transversal study with a descriptive purpose over 5 years from 2012 to 2016 in the Gynecology and obstetrics department of UH-C. The studied population was all cases of genital prolapse diagnosed and treated in the service during the period of the study. A follow-up over one year after surgery has been observed to evaluate surgical outcomes and recurrences. Genital prolapse was generally a uterine prolapse at stage 3 or 4. It was associated to cystocele in 31.4%. We did not find stress urinary incontinence associated with prolapse in our study. The surgical intervention performed was, in the majority case, the triple perineal intervention with success of 95.6%. A case of recurrence in the form of cystocele has been observed to a year of decline. Results: Genital prolapse was relatively common. It accounted for 0.5% of all gynecological visits. Women were young with an average age of 39.5 years. 62.9% were multiparous. 62.5% had given birth at least once at home without medical assistance. The reason for consultation the most watched was the projection of body at the vulva. Conclusions: Genital prolapse is a condition under estimated in Côte d'Ivoire. It represented 0.5% of the gynecological visits. Obstetric traumas were frequently found in our young patients with genital prolapse. The sociocultural considerations have contributed to delay consultations, to observe very advanced stages. The surgery performed was mainly the perineal triple surgery.